The Story of Moses and Pharaoh in a Structural Anthropology Approach - Ahmad Umam Aufi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This study examined the story of Moses and Pharaoh as one of the Islamic narrative discourses in the Qur’an. Structural anthropology Claude Lévi-Strauss was used to analyze the story’s structure or nature of the mind. The results of the study explicate that the story of Moses and Pharaoh had a structure of “struggle plot to convey the truth”. Based on the episodes of the story showed a continuous transformation of structure and forms cylindrical triangle. Behind the story of Moses and Pharaoh was reflection of the developing culture in Islamic societies. First, there were some societies’ components in the struggle process of the faithful in conveying the truth, both theologically or socio-politically. Such as the actor of social change (Moses), masses of people (the people of Moses), authorities who refused the change (Pharaoh and his leaders) and opportunist intellectuals (the magicians before being defeated by Moses), and organic intellectuals (the magicians after believing in the truth of Moses). Second, the community’s culture was controlled by established authorities, the commitment of the truth will gain a refusal and despite resistance. The prerequisite to be able to undergo it was to confirm it rationally and empirically (according to the times).